ผลของอีดีทีเอและอีดีดีเอสต่อการดูดดึงโครเมียมและตะกั่วโดยใช้สับปะรดที่ปลูกในดินปนเปื้อน - ทิพวรรณ พจนาภรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The effects of chelating agents on chromium and lead absorption were studied by planting pineapple, Ananas comosus (L.) Merr. in contaminated soil. All plant samples were grown in a nursery for 30 days then plant samples were separated into seven sets. Set 1) did not have anything added (Blank), 2) this set had only added chromium, Potassium dichromate (K2Cr2O7), at the rate of 400 milligrams per kilogram soil, 3) this set had added Potassium dichromate and Ethylene Diamine Tetraacetic Acid (EDTA),) one of the chelating agents, 4) this set contained both Potassium dichromate and Ethylene Diamine Dissucinate (EDDS), the second chelating agent, 5) this set had only added Lead(II)nitrate (Pb(NO3)2), at the rate of 500 milligrams per kilogram soil 6) this set was treated with both Lead(II)nitrate and Ethylene Diamine Tetraacetic Acid (EDTA) and 7) this set contained both Lead(II)nitrate and Ethylene Diamine Dissucinate (EDDS). The chelating agent’s concentration was 2 millimole per kilogram soil. Soil and plant contamination was determined by analyzing the total chromium (Total Cr), chromium hexavalance (Cr(VI)) and total amount of lead (Total Pb) 30, 60, 90 and 120 days after planting. The analysis divided the plant samples into aboveground and underground parts. Plants were also analyzed by dry weight, root length and expressions of toxicity, withered leaves and yellow leaf symptoms. The results of this study showed that the EDTA agent had the highest lead absorption efficiency with the plant sample absorbing 288.14 milligrams of lead per kilogram in aboveground part, and 796.66 milligrams per kilogram in underground part after 60 days. The EDTA agent also had high chromium absorption efficiency with plant sample absorbing chromium at 545.72 milligrams per kilogram in aboveground part, and 2,267.99 milligrams per kilogram in underground part after 90 days. Moreover, the EDTA agent caused higher chromium and lead accumulation and higher chromium and lead absorption efficiency from contaminated soil than the EDDS agent. The EDTA and EDDS agents did not affect pineapple growth. Expression of toxic symptoms were statistically significant with relationships of 0.05 (P ≤ 0.05) compared with control sets.